2008
DOI: 10.1111/j.1460-9568.2008.06138.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning‐related changes in reward expectancy are reflected in the feedback‐related negativity

Abstract: The feedback-related negativity (FRN) has been hypothesized to be linked to reward-based learning. While many studies have shown that the FRN only occurs in response to unexpected negative outcomes, the relationship between the magnitude of negative prediction errors and FRN amplitude remains a matter of debate. The present study aimed to elucidate this relationship with a new behavioural procedure that allowed subjects to predict precise reward probabilities by learning an explicit rule. Insight into the rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
220
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(256 citation statements)
references
References 41 publications
28
220
6
Order By: Relevance
“…When asked about feedback frequencies, 11 of 20 participants believed that positive feedback had been less frequent than negative feedback, while only four subjects believed the opposite. Although previous studies examining reward processing have led to inconsistent results, linking the P300 to reward magnitude regardless of valence (Yeung and Sanfey, 2004;Sato et al, 2005) or negative valence (Frank, 2005), the present results are in line with findings that P300 is larger after positive events (Hajcak et al, 2007;Bellebaum and Daum, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When asked about feedback frequencies, 11 of 20 participants believed that positive feedback had been less frequent than negative feedback, while only four subjects believed the opposite. Although previous studies examining reward processing have led to inconsistent results, linking the P300 to reward magnitude regardless of valence (Yeung and Sanfey, 2004;Sato et al, 2005) or negative valence (Frank, 2005), the present results are in line with findings that P300 is larger after positive events (Hajcak et al, 2007;Bellebaum and Daum, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Rather, our concern is with the differing predictions the theories make about the functional properties of the FRN response. We additionally examined another ERP correlate of performance moni-toring, the P300, which has been shown to vary with the frequency and valence of feedback stimuli (Bellebaum and Daum, 2008). For this purpose, the electroencephalogram was recorded during a time-estimation task with positive, negative, and intermediate feedback.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, empathy has been shown to be modulated by gender [5,36], fairness [5] and emotional sensitivity towards others [4,5,37]. On the other hand, the evaluative component could be modulated by other factors, such as magnitude [38], probability [39] or amount of information provided by the feedback [40]. Importantly, in the reverse condition the two components would compete: whereas the empathic component would lead to an FRN in response to the other's loss, the evaluative component would trigger an FRN to one's own loss (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has repeatedly demonstrated that neural mechanisms involved in such performance monitoring functions are subject to action-outcome expectancies. In particular, numerous recent studies have shown that electrocortical correlates of performance monitoring in the scalp-recorded electroencephalogram (EEG) are sensitive to the predictive value of cue stimuli preceding action outcomes (e.g., Bellebaum & Daum, 2008;Chase, Swainson, Durham, Benham, & Cools, 2011;Hauser et al, 2014;Hewig et al, 2007;Martin & Potts, 2011;Mas-Herrero & Marco-Pallarés, 2014;Pfabigan, Alexopoulos, Bauer, & Sailer, 2011;Pfabigan et al, 2015;Potts, Martin, Burton, & Montague, 2006;Walsh & Anderson, 2011;Wu & Zhou, 2009;Xu et al, 2011). In the majority of these studies, the indicative cues were simple visual stimuli like, for instance, geometrical shapes, letters, or colors.…”
Section: Introductionmentioning
confidence: 99%